2020
DOI: 10.1111/cpr.12768
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between RNA N6‐methyladenosine methyltransferase‐like 3 and miR‐186 regulates hepatoblastoma progression through Wnt/β‐catenin signalling pathway

Abstract: Objectives N6‐methyladenosine (m6A) is a ubiquitous epigenetic RNA modification that plays a pivotal role in tumour development and metastasis. In this study, we aimed to investigate the expression profiling, clinical significance, biological function and the regulation of m6A‐related genes in hepatoblastoma (HB). Materials and Methods The mRNA and protein expression levels of m6A‐related genes were analysed using Gene Expression Omnibus (GEO) and tissue microarray (TMA) cohort. Kaplan‐Meier analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 43 publications
3
84
0
Order By: Relevance
“…As the most common pediatric liver cancer, hepatoblastoma (HB) has also been reported to have aberrant m 6 A modification [60,81]. Liu et al found that METTL3 was significantly upregulated in HB, inducing enhanced m 6 A modification across the whole transcriptome.…”
Section: Liver Cancermentioning
confidence: 99%
“…As the most common pediatric liver cancer, hepatoblastoma (HB) has also been reported to have aberrant m 6 A modification [60,81]. Liu et al found that METTL3 was significantly upregulated in HB, inducing enhanced m 6 A modification across the whole transcriptome.…”
Section: Liver Cancermentioning
confidence: 99%
“…Emerging evidence has widely confirmed the critical role of miRNAs in tumorigenesis. MiRNAs could promote carcinogenesis through targeting tumor suppressor genes or inhibit tumor development by suppressing oncogenes [12][13][14][15][16] . MiR-145-5p has been characterized as a tumor suppressor in gastric cancer 17 , colorectal cancer 18 , breast cancer 19 , and bladder cancer 20 .…”
Section: Introductionmentioning
confidence: 99%
“…METTL3 was considered to be a methyltransferase, part of the methyltransferase complex, and was responsible for the m6A modi cation [27,53].METTL3 was involved in many signal pathways such as PI3K / Akt [31,[54][55][56][57][58], MAPK [22] ,Wnt /beta-Catenin [47,59,60] and p38 / ERK [61]pathways,which were all associated with tumor deterioration. In addition, METTL3 could in uence the development of tumor by regulating some transcription factors or important oncogenes.Studies had found that METTL3 could positively regulate the expression of oncogene EZH2 [24,25,62].It promoted the expression of MYC as well as increased stability of protein by regulating the m6A methylation of MYC mRNA to lead to carcinogenesis in PCA and gastric cancer, promote the occurrence of OSCC tumor and affect the growth and invasion of BCA cells [40,[63][64][65][66].When METTL3 was silenced, it inhibited the activity of the Wnt pathway by reducing the m6A methylation level of LEF1 mRNA and reducing protein expression [59,67].…”
Section: Discussionmentioning
confidence: 99%
“…The studies were screened according to the following procedure [19,[39][40][41][42][43][44][45][46][47][48] (Fig. 1).At rst We retrieved a total of 349 articles from the online database.After preliminary screening and duplicate checking, 253 articles were retained.Through reading the title and abstract of the articles, the articles were further screened.Studies of 207 related to METTL3 expression and cancer prognosis were excluded according to exclusion criteria.…”
Section: Eligible Researchesmentioning
confidence: 99%